AN ASSESSMENT OF COMMUNITY POLICING-ORIENTED TRAINING PROGRAMME IN BENUE AND LAGOS STATES, NIGERIA (2014)
The adoption of community policing-oriented strategy in Nigeria in 2004 has led to a shift in police training focus and curriculum contents. Studies on community policing-oriented training have largely been general in nature without paying much attention to the training content, competence of trainers and post-training challenges. This study therefore, assessed the perceived influence of community policing-oriented training on police interactions with the public in crime prevention in Benue and Lagos States. A combination of gap, community-driven development and skill acquisition theories were adopted as theoretical framework. Ex-post-facto research design was employed. The capitals of Benue and Lagos states were purposively selected, with the police and community leaders constituting the study population. Six divisional police headquarters were selected from each of the two locations through a purposive sampling method. The questionnaire focused on demographic data, policing experience of respondents, adequacy, relevance and challenges of community policing-oriented training in Nigeria. Questionnaire was administered to 600 respondents selected through simple random sampling method, while post-training observations, twenty one in-depth interviews (IDI) and six Focus Group Discussions (FGD) sessions were conducted among purposively selected police trainers, divisional police officers and key community leaders. Quantitative data were analysed using descriptive statistics, Chi-square test, and T-test while qualitative data were content-analysed. The respondents’ mean age was 34±6 years, 65.0% were males and 52.0% had secondary education. Respondents with 1-5 years of policing experience were 41.8%. Perceived friendliness of the public to the police was 23.7% and 89.0% before and after training respectively. There was a significant relationship between years of policing experience and the perceived relevance of training materials to daily policing experience (p<0.05). There was a significant relationship between years of policing experience and effectiveness of community policing-oriented training in crime prevention among the trainees p<0.05). The curriculum for training was considered relevant within the backdrop of community policing-oriented training objectives revolving mainly around human rights, communication, leadership, intelligence gathering, conflict management, community engagement, attitudinal change, accountability, vigilante support and relationship-building skills. The practical component was not undertaken as training modules were designed mainly for use in the class rooms. However, post-training field observation indicated the complaints of unfriendly attitude on the part of officers towards the public. The IDI showed poor treatment of the public, logistics and welfare concerns by the police. The FGD showed that the complaints of extortion, disrespect, corruption and brutality by the public still persisted, while the police post-training challenges included posting trainees to crime fighting beats, skeptical public, uncooperative colleagues and lack of equipment and kits from the government. The public in Benue state were more eager to partner with the police in crime prevention than the Lagos state public. The police in Benue and Lagos states have embraced community policing-oriented training programme, but their attitude towards the public have not improved. There is therefore a need to expose trainees to practical demonstrations of crime prevention in the community to make them relate better with the public.